Modeling ocean circulation and biogeochemical variability in the Gulf of Mexico - Z. Xue; R. He; K. Fennel; W.-J. Cai; S. Lohrenz; C. Hopkinson (Biogeosciences, 2013)
A three-dimensional coupled physical-biogeochemical model is applied to simulate and examine temporal and spatial variability of circulation and biogeochemical cycling in the Gulf of Mexico (GoM). The model is driven by realistic atmospheric forcing, open boundary conditions from a data assimilative global ocean circulation model, and observed freshwater and terrestrial nitrogen input from major rivers. A 7 yr model hindcast (2004–2010) was performed, and validated against satellite observed sea surface height, surface chlorophyll, and in situ observations including coastal sea level, ocean temperature, salinity, and dissolved inorganic nitrogen (DIN) concentration. The model hindcast revealed clear seasonality in DIN, phytoplankton and zooplankton distributions in the GoM. An empirical orthogonal function analysis indicated a phase-locked pattern among DIN, phytoplankton and zooplankton concentrations. The GoM shelf nitrogen budget was also quantified, revealing that on an annual basis the DIN input is largely balanced by the removal through denitrification (an equivalent of ~ 80% of DIN input) and offshore exports to the deep ocean (an equivalent of ~ 17% of DIN input).